Revised Self-Monitoring Scale: A potential endpoint for frontotemporal dementia clinical trials. (2nd June 2020) - Toller, Gianina; Ranasinghe, Kamalini; Cobigo, Yann; Staffaroni, Adam; Appleby, Brian; Brushaber, Danielle; Coppola, Giovanni; Dickerson, Bradford; Domoto-Reilly, Kimiko; Fields, Julie; Fong, Jamie; Forsberg, Leah; et al.
Abstract : Objective: To investigate whether the Revised Self-Monitoring Scale (RSMS), an informant measure of socioemotional sensitivity, is a potential clinical endpoint for treatment trials for patients with behavioral variant frontotemporal dementia (bvFTD). Methods: We investigated whether RSMS informant ratings reflected disease severity in 475 participants (71 bvFTD mutation+, 154 bvFTD mutation−, 12 behavioral mild cognitive impairment [MCI] mutation+, 98 asymptomatic mutation+, 140 asymptomatic mutation−). In a subset of 62 patients (20 bvFTD mutation+, 35 bvFTD mutation−, 7 MCI mutation+) who had at least 2 time points of T1-weighted images available on the same 3T scanner, we examined longitudinal changes in RSMS score over time and its correspondence to progressive gray matter atrophy. Results: RSMS score showed a similar pattern in mutation carriers and noncarriers, with significant drops at each stage of progression from asymptomatic to very mild, mild, moderate, and severe disease (F 4, 48 = 140.10, p < 0.001) and a significant slope of decline over time in patients with bvFTD ( p = 0.004, 95% confidence interval [CI] −1.90 to −0.23). More rapid declines on the RSMS corresponded to faster gray matter atrophy predominantly in the salience network (SN), and RSMS score progression best predicted thalamic volume in very mild and mild disease stages of bvFTD. Higher RSMS score predicted more caregiver burden ( p < 0.001, 95% CI −0.30 to −0.11). Conclusions: The RSMS is sensitive to progression of both socioemotional symptoms and SN atrophy in patients with bvFTD and corresponds directly to caregiver burden. The RSMS may be useful in both neurologic practice and clinical trials aiming to treat behavioral symptoms of patients with bvFTD.